2023
DOI: 10.1101/2023.06.02.543359
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic diversity, determinants, and dissemination ofBurkholderia pseudomalleilineages implicated in melioidosis in northeast Thailand

Abstract: Melioidosis is an often-fatal neglected tropical disease caused by an environmental bacterium Burkholderia pseudomallei. However, our understanding of disease-causing bacterial lineages, dissemination, and their adaptive mechanisms remains limited. To address this, we conducted comprehensive genomic analysis of 1,265 B. pseudomallei isolates collected from nine hospitals in northeast Thailand between 2015 and 2018, presenting the most densely sampled collection to date. Our study identified four dominant linea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Given different units of genetic variations (gene presence, unitig, and SNP), and a binary disease outcomes (estimated 30% mortality), we used an additive model 32 to calculate the sample size with different MAF. Using a genome-wide significant cut-off at 5 × 10 -8 and genotype relative risk of 1.5, our combined size of over 2,400 B. pseudomallei genomes collected in the same endemic area under this study and those reported in 6 , 30 , 33 has sufficient power to detect associations with MAF of 0.15 ( Figure 2c ).…”
Section: Protocolmentioning
confidence: 89%
“…Given different units of genetic variations (gene presence, unitig, and SNP), and a binary disease outcomes (estimated 30% mortality), we used an additive model 32 to calculate the sample size with different MAF. Using a genome-wide significant cut-off at 5 × 10 -8 and genotype relative risk of 1.5, our combined size of over 2,400 B. pseudomallei genomes collected in the same endemic area under this study and those reported in 6 , 30 , 33 has sufficient power to detect associations with MAF of 0.15 ( Figure 2c ).…”
Section: Protocolmentioning
confidence: 89%